Wastewater treatment and sludge disposal for small communities in cold climates - (:unkn) unknown (Nazarbayev University, 2013)
This research project investigates a new type of wastewater treatment process for cold climates consisting of Primary Settling, Activated Sludge, Clarifier and separate Biological Aerated Filters based on fixed biofilms to address nitrification requirements. The objective of the research is to determine the reliability, robustness and resilience to meet the specific needs of small communities in cold climates.
Keywords: first research week; wastewater treatment; Biological Aerated Filters